RESEPSI KASIDAH BURDAHAL BOSHiRY DALAM MASYARAKAT PESANTREN - Fadlil Munawwar Manshur, Fadlil (l:akllltlHI llrnu BudavaUniversitasGadlahMada, 2006)
Qashldah8urdahisareligiousliterarywork thatgot anhonorreceptionfrom thepeoplearoundthe world. Therefore, it is no wonder thatQashfdah8urdahcould attract wide Interest from the world communityin the form ofscientificstudy:Qashldah8urdahrecitalinthereligiousceremony;consumer's receptionIntherecordingindustryandartperformance,commentsandtranslationfrom theArabicinto variouskindsof the worldlanguages: English,French,Spanish,Italian, Dutch,andGerman.The Nordic languages coverof Norway,Sweden,Denmark,Iceland, andFinland.The nextisRussian,Turk,Persian, Urdu,Swahili,Chinese,Indonesian andotherlanguages in Nusantara,l.e.,Sundanese,Javanese,and Acehnese.